2018
DOI: 10.1016/j.buildenv.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Can a naturally ventilated office outperform a mixed mode office? Pilot study on occupants' comfort

Abstract: Abstract:It is established that a mixed mode indoor environment provides the best for occupant comfort by augmenting the passive system with a mechanical system when and where required. However, the recent desperation for near zero energy environments, of which natural ventilation provides, warrants the need to explore the possibility of achieving this without sacrificing occupants' comfort. The purpose of this study was to investigate if a naturally ventilated building can outperform a mixed mode building in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The Building Use Studies (BUS) methodology, likewise, contains 45 with 7-point ratings scales for 11 IEQ categories such as temperature, noise, lighting, and appearance [21][22][23]. One study used BUS to assess 47 buildings (from offices to healthcare facilitates) in the United Kingdom and found this methodology highly reliable, with Cronbach's alpha values over 0.9 for all IEQ criteria [21].…”
Section: Workplace Occupancy Evaluation Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The Building Use Studies (BUS) methodology, likewise, contains 45 with 7-point ratings scales for 11 IEQ categories such as temperature, noise, lighting, and appearance [21][22][23]. One study used BUS to assess 47 buildings (from offices to healthcare facilitates) in the United Kingdom and found this methodology highly reliable, with Cronbach's alpha values over 0.9 for all IEQ criteria [21].…”
Section: Workplace Occupancy Evaluation Researchmentioning
confidence: 99%
“…BUS findings highlight that hours of using visual display units (i.e., monitors) left negative impacts on occupant satisfaction (r = -0.050 to r = -0.117, across buildings), with p < 0.0001. Another BUS study conducted in two office buildings (n = 138) in New Zealand revealed that light, ventilation, and open spaces (79%) enhance occupant satisfaction, while temperature (76%) and noise (50%) hindered occupant performance [22].…”
Section: Workplace Occupancy Evaluation Researchmentioning
confidence: 99%
“…During the last decade, thermal comfort research has seen a revival of natural ventilation (NV) as a passive design strategy to reduce cooling and ventilation energy demand [1,2], while providing pleasant thermal environments [2][3][4][5][6] and reducing the possibility of sick building syndrome [7,8]. NV uses temperature differences or wind pressure differentials to supply and remove air across ventilation openings to and from indoor spaces [9], without the adoption of mechanical systems to drive air movement (e.g., fans).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lack of studies prevents the potential regenerative impact from enhancements in building performance and reductions in energy consumption through airflow analysis. Well-designed buildings employing natural ventilation can provide comfort better than mixed-mode buildings [29].…”
Section: Cfd Analysis Of Residential Airflow Through Natural Ventilationmentioning
confidence: 99%